Relegitimizing Religious Authority: Indonesian Gender-Just ʿUlamāʾ Amid COVID-19 - Eva F. Nisa; Farid F. Saenong (Religions, 2022)
Studies have highlighted the increased vulnerability of women during and after disasters. Thus, there has been a call for gender-aware disaster management—an approach which is certainly needed, especially when a patriarchal culture is embedded in a society. Unfortunately, studies on women as vulnerable agents are often not balanced against careful examinations of instances where women help women. Drawing on (digital) ethnography conducted between 2020 and 2022, this article focuses on analysing the voices and activities of gender-just ʿulamāʾ (Muslim scholars) in Indonesia during the COVID-19 pandemic. The COVID-19 pandemic, which has affected traditional religious gathering practices, has led to creative solutions to social proximity restrictions. Many ʿulamāʾ have been “forced” by the situation to adjust to digital religion. This article analyses how female religious authorities who colour the daily daʿwa (proselytization) landscape in Indonesia deal with the uncertainties brought on by the pandemic. The daʿwa scene in Indonesia has long been the site of contention among various competing ideological understandings. The pandemic and the proliferation of digital religion has led gender-just ʿulamāʾ to relegitimize their authority through an online presence so they can compete and counter the narratives of tech-savvy conservative Muslims.